Implementasi Pengiriman Suara Melalui Serat Optik dengan menggunakan LED yang Berbeda - Ummi Hafidhotunnisa (Jurnal Jaringan Telekomunikasi, 2019)
Optical fiber is a transmission medium for sending information that uses light as a source of information. Optical fiber can be used as a transmission medium to transmit information in the form of data, video and voice. Of the various kinds of light sources used, the most bpouler used is laser. Even though there are still many light sources used, namely leds. In this research, the design of a sound transmission transmission system is designed, but by using a led light source with different colors. With different colors means the wavelength of the led is also different. This affects the amount of information conveyed at the receiving end. The results showed unsatisfactory results, due to the limited standard of existing components and the angle of light reception that did not meet the standards from the optical fiber reception angle. However, there are several results from the study, namely the value of reinforcement from the sender's side has a difference of 2.4. In the measurement of the SNR value, the SNR value of the LED is greater than the SNR value of the laser when without using a cable of 0.1387 and when using a measuring cable of 3.5924 x 10-5. Then also generated a reinforcement response to changes in the frequency value. The greater the frequency value, the lower the gain.